Estimated inorganic arsenic from total arsenic in fishery products and its health risk to the Indonesian population - Dwiyitno Dwiyitno; Nuri Andarwulan; Hanifah Nuryani Lioe; Nelis Imanningsih; Puspo Edi Giriwono; Deksa Presiana; Rina Adriany; Eva Nikastri; Novi Pusparini; Ilaine Audia; Ninda Nur Amaliya; Famila Takhwifa (Emerging Contaminants)
The present study is the first assessment of inorganic arsenic exposure from various fishery products to the Indonesian population based on a national total diet study (TDS). Based on the TDS report on food chemical contaminants, fish and processed fishery products are among the foodstuffs significantly contributing to total arsenic (t-As) exposure in Indonesia. However, there is no assessment yet for the Indonesian population to inorganic arsenic (i-As), which is known as the most harmful of arsenic compounds as it potentially promotes acute and chronic poisoning. The present assessment is aimed to estimate the exposure to i-As from fish and processed fishery products as well as the level of health risks in different age groups in Indonesia, based on the available t-As concentration data. The results showed that the mean exposure to t-As and i-As from fish and processed fishery products in various age groups were 1.19–2.67 μg/kg bw/day and 0.04–0.08 μg/kg bw/day, respectively. Exposure in various age groups revealed that the highest arsenic exposure was in toddlers (0–4 years) and the lowest in the age group of 19–55 years. Wet seasonings and marine fish consumption led to the most contributors to i-As exposure. The carcinogenic risk of i-As exposure based on the margin of exposure (MOE) demonstrated a low to moderate risk. However, a particular concern to the toddler group is required as the cancer risk (CR) value is higher than the acceptable threshold (>10−4). Additionally, the hazard quotient (HQ) of i-As exposure was determined as a low possibility of chronic risk.